방송산업의 시장 획정과 제도 분석 - 이수일 (한국개발연구원, 2009)
This study defines relevant markets with its target on main economic transactions that exist in the broadcasting industry. Based on the definitions, the study analyzes the adequacy of existing systems and the necessity of a new system. Foremost, the study defines markets relating to transactions of broadcast channels and access to viewers between terrestrial broadcasters and platform service providers. The result suggests a high possibility that terrestrial broadcasters may hold a unilateral monopoly in the ongoing negotiation over the retransmission fee of digital terrestrial channels. In this context, to limit the market dominance of terrestrial broadcasters and encourage fair competition among platform service providers, this study presents policy measures to adopt the must-offer system-which designates main terrestrial channels as mandatory channels-and of making it mandatory to use the same methodology in calculating the retransmission fee. Then, the study further suggests a etransmission fee-calculating method that could maximize fair and various social welfare functions for both terrestrial broadcasters and platform service providers, along with detailed explanation of calculation process. Thereafter, the study defines markets relating to each paid broadcasting service by applying the test method of critical sales loss to the results of survey to the paid service subscribers. The result confirms the existence of a meaningful competitive elationship-in terms of the Competition Law-among all paid broadcasting services included in this study, or at least analog cable broadcasting, digital cable broadcasting, and real time IPTV service. This indicates that current regulations which are being applied to cable TV, satellite broadcasting, and IPTV are actually discriminative. Based on these analysis results, this study suggests the improvement direction for regulations differently applied to different platform service providers, such as the contents equal access rule and the market-share limitation regulations on platform service providers stipulated in the Internet Multimedia Broadcasting Law and the Broadcasting Law.